A new biodiesel production by water addition to supercritical tert-butyl methyl ether using a plug flow reactor. (1st December 2021) - Ridwan, Iwan; Chinwanitcharoen, Charoen; Tamura, Kazuhiro
Graphical abstract: Highlights: Biodiesel was synthesized from rapeseed oil, MTBE, and water. The supercritical reaction was carried out in a plug flow reactor. Biodiesel yield of 77.39% was achieved at water of 8.2 wt% and 300 °C in 30 min. The water on supercritical MTBE improves kinetics parameters. The reaction is endothermic, endergonic, and unspontaneous. Abstract: The water addition to supercritical tert -butyl methyl ether for continuous biodiesel production from rapeseed oil has been carried out to promote an essential enhancement of biodiesel yield. We developed a new biodiesel production by supercritical tert -butyl methyl ether with water and evaluated process variables influence using response surface methodology to obtain an optimum condition. We found that the optimum condition was at water addition of 25 wt%, temperature of 300 °C, and pressure of 20 MPa at space time of 30 min to achieve 77.39 wt% of biodiesel yield. In addition, the reaction rate constants were determined by first-order reaction model. We suggested that water addition to the supercritical tert -butyl methyl ether accelerates reaction rate and diminishes activation energy since the water acts as a catalyst for the reaction. The thermodynamic parameters were calculated using Eyring-Polanyi equation based on the transition state theory. We found that the supercritical reaction was endothermic, endergonic, and non-spontaneous.